PERBANDINGAN KEBERHASILAN IMPLEMENTASI PROGRAM DESA DAN KELURAHAN SIAGA AKTIFDESA NYALEMBENG DAN DESA GAMBUHAN KABUPATEN PEMALANG TAHUN 2015 - Arinta Sistyanika; Ahmad Taufiq; Wachid Abdulrahman (Journal of Politic and Government Studies, 2017)
ABSTRACTProgram of active standby village and active standby urban village are development from active standby program that is launched by The Ministry of Health Republic of Indonesia. The core idea of this project is empowering society so they want and be able to solving health problem. The aims of this research is to describe the difference in successful implementation of active standby village and urban village program in Nyalembeng and Gambuhan Village, Pulosari Sub-district, Pemalang Regency of the year 2015. Beside that, this research also aims to identify any factors that causing difference in successful implementation active standby village and urban village program in Nyalembeng and Gambuhan Village in 2015.The method of the research that be used is qualitative approach with collecting data technic consist of observation, interview, and documentation. Informants in this research are Head of Section of Health Promotion and Health Care Insurance of Public Health Pemalang Health Department, Head of Nyalembeng and Gambuhan Village, Midwife of Nyalembeng and Gambuhan Village, Head of FKD (Village Health Forum) Nyalembeng and Gambuhan Village, Health Cadre of Nyalembeng and Gambuhan Village, and also society of Nyalembeng and Gambuhan Village.The result of the research showed that the implementation of active standby village and urban village program in Nyalembeng Village of the year 2015 have been running optimally. The implementation that have been optimally running was supported by existing resources whom have already adequate to supporting the implementation of active standby village and urban village program in Nyalembeng Village. While, the implementation of active standby village and urban village program in Gambuhan Village have not optimally running yet caused by less adequate resources which hamper the implementation of active standby village and urban village program in Gambuhan Village.Keywords: Active Standby Village, Comparison, Implementation